Digital Twin-Driven Virtual Cinematography: Statistical Analysis of Camera Techniques for Enhanced Narrative Engagement in Drama Production - Ramadhani, Nugrahardi; Prasetyo, Didit; Hariadi, Mochamad; Khrisna Wardhani, Anindya; Rizky Mutiaz, Intan (Engineering, Technology & Applied Science Research, 2025)
Camera techniques and angles are essential for shaping the visual narrative of digital media productions, especially in dramatic films. The traditional methods for selecting the best camera angles often depend on subjective decisions, leading to expensive and time-consuming trial-and-error processes. This study presents a novel approach using the Digital Twin (DT) technology to simulate and evaluate the effects of various camera techniques and angles in a virtual production environment. A two-way Analysis of Variance (ANOVA) was employed to investigate the impact of nine imaging techniques and three camera angles (X, Y, Z) on the cinematic quality. The results indicate that the Y-axis angle has a significant influence on the visual and emotional impact of dramatic scenes, with an F-value of 36,305.71 and a p-value of 0.000, indicating a strong relationship. Additionally, the interaction between the camera distance and angle demonstrated a significant effect, with an F-value: 198.07 and p-value: 0.000. By leveraging the DT simulations, filmmakers can reduce the production costs by up to 30% and improve the decision-making efficiency during pre-production. This research establishes a groundbreaking framework for integrating data-driven virtual production into filmmaking, providing a systematic and scalable method to enhance cinematic storytelling.